2007
DOI: 10.1159/000099846
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Alexithymia and Type A Behavior in Coronary Heart Disease Patients: A Multimethod Approach

Abstract: Background: Despite increasing emphasis on using multiple methods to assess personality constructs in psychosomatic research, previous investigations of relations between alexithymia and type A behavior (TAB) have been limited by the use of single methods of measurement and almost no attempt to assess subcomponents of TAB. The aims of this study were to (1) evaluate levels of agreement between structured interview assessments of alexithymia, TAB, hostility, and time urgency and well-established self-report mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…In addition, the results showed that alexithymia is indirectly involved in predicting QOL in patients with CHD with the mediating role of psychological distress. These findings are consistent with previous studies (7,15,20,41). To explain these findings, it has been argued that alexithymia increases misconceptions of the patients about their disease and results in deteriorated of QOL (41).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the results showed that alexithymia is indirectly involved in predicting QOL in patients with CHD with the mediating role of psychological distress. These findings are consistent with previous studies (7,15,20,41). To explain these findings, it has been argued that alexithymia increases misconceptions of the patients about their disease and results in deteriorated of QOL (41).…”
Section: Discussionsupporting
confidence: 91%
“…Alexithymia refers to disability in identifying, processing, or describing feelings, and difficulty in differentiating feelings with physical and emotional arousal (15). Alexithymia is generally associated with health problems such as heart diseases (20,21). Moreover, alexithymia can disrupt QOL in patients with physical diseases (22).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, conscientiousness was related to the adoption of healthy attitudes measured by the health habits scale [53]. Alexithymia, the inability to use appropriate words to describe emotions with a resulting utilitarian way of thinking [82,83,84,85,86,87], also showed a positive relationship with the IAS scores [46, 88]. These results were found both in normal subjects and in clinical samples recruited in medical or psychiatric settings.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, psychological assessment with DCPR was found to be more suitable than DSM-IV criteria in identifying somatization in patients with functional gastrointestinal disturbances or cardiac disease [76]. Further, the use of DCPR has disclosed that not all coronary artery disease patients display type A behavior, and, vice versa, that type A behavior is present in other settings including dermatology, gastroenterology, cancer patients and frequent attenders of primary care [48, 77, 78]. …”
Section: Expanding the Spectrum Of Psychosocial Assessmentmentioning
confidence: 99%